Surface plasmon-driven electron and proton acceleration without grating coupling. (1st July 2022) - Sarma, J; McIlvenny, A; Das, N; Borghesi, M; Macchi, A
Abstract: Surface plasmon (SP) excitation in intense laser interaction with solid target can be exploited for enhancing secondary emissions, in particular efficient acceleration of high charge electron bunches. Previous studies have mostly used grating coupling to allow SP excitation, which requires stringent laser contrast conditions to preserve the structural integrity of the target. Here we show via simulations that efficient SP electron acceleration for currently available short pulse lasers can occur in a flat foil irradiated at parallel or grazing incidence ( ∼ 5 ° with the target surface) without a surface modulation. In turn, the accelerated electrons can be effective for generating proton beams with narrow spectra peaked at > 100 MeV energies for currently available laser drivers.